A survey of Sumatran Ctenidae (Araneae). 2. Three new species of Bowie Jäger, 2022 - Omelko, Mikhail M.; Fomichev, Alexander A. (Zootaxa, 2023)
Three new species, Bowie beruang sp. nov., B. binturong sp. nov., and B. dhole sp. nov., are described from Sumatra (Indonesia). Each species description is based on both sexes. Detailed descriptions, digital photographs and a distributional map are provided.